Characteristics of severe intraocular inflammation following intravitreal injection of bevacizumab (Avastin). Issue 4 (25th November 2008) - Georgopoulos, M; Polak, K; Prager, F; Prünte, C; Schmidt-Erfurth, U
Abstract : Background/aims: To report a series of severe intraocular inflammatory events following intravitreal injections of bevacizumab (Avastin). This procedure is performed on a rapidly increasing number worldwide, and rare complications such as intraocular inflammation, endophthalmitis or intraocular haemorrhage are gaining in importance in clinical routine. Methods: This is a single-centre retrospective interventional case series of eight patients with severe intraocular inflammation after intravitreal injection of bevacizumab at one referral centre consecutively seen out of approximately a total of 2500 injections performed in that time period. Patients who developed severe intraocular inflammation after intravitreal injection were evaluated clinically, including slit-lamp examination, best-corrected Snellen visual acuity (VA), slit-lamp photography, optical coherence tomography and fluorescein angiography prior to the event and during follow-up. Results: Patients noticed a painless drop in VA up to 2 days following the injection. All patients had a marked anterior chamber reaction with increased flare and cells, but no hypopyon. Typical posterior segment findings included vitreous cellular infiltrates of pseudogranulomatous aspect. Due to their initial clinical aspect suspicious of an endophthalmitis, three cases were treated with systemic antibiotics, but the final diagnosis was uveitis. Five cases showed a characteristic pseudogranulomatous vitreous infiltration as seen in vitritis and were treated only topically. Conclusions: Characteristic features of an inflammation induced by bevacizumab injection include an early onset with painless loss in VA mostly without conjunctival or ciliary injection. Patients respond to systemic or topical cortisone treatment with slow recovery but without permanent damage. Vitreous haemorrhage and infectious endophthalmitis might be differentiated by time course and symptoms.